Corruption, democracy, and human rights: A relationship under development - Figueroa Gutarra, Edwin (2023)
The relationship between democracy and human rights are often progressive, in contrast to corruption, a historical phenomenon that poses regressive conditions. Establishing a link between these three concepts necessarily leads us to an attempt to reinforce democracy, as well as a desire to make human rights more effective. Therefore, reducing the harmful effects of corruption is now an urgent task for every Government, and from then on, to constantly rethink the measures needed to be taken. These are urgent challenges.